Students Meeting with Caregivers of Cancer Patient: Results of an Experience-Based Learning Project - ATASOY, BESTE MELEK; KUŞCU, MEHMET KEMAL; SARIKAYA, ÖZLEM (SPRINGER, 2012)
The communication between medical students and cancer caregivers, and the problems they have experienced as well as the outcomes for their professional development before starting clinical practice was assessed in the context of a student research project. Data were collected by questionnaires or by 20 to 40-min long interviews with cancer caregivers. Their communications with physicians, hearing the bad news, and health service satisfaction were questioned. Therefore, the caregivers trusted the professional approach of their physician. However, they expected more empathic communication in the process of diagnosis and therapy. Development of empathy and trust-based communication between patients and physicians and enhancement of the quality of devoted time to cancer patients and caregivers may have an effect on the course of disease. Interviewer students mentioned that they developed communication skills about difficult clinical tasks and in delivering bad news face to face to cancer caregivers before starting their clinical education.
Keywords: Action research; Breaking bad news; Cancer caregiver; Experiential learning; PHYSICIAN EMPATHY; HEALTH OUTCOMES; PRIMARY-CARE; COMMUNICATION; EDUCATION; PROFESSIONALISM; PRACTITIONERS; ONCOLOGY; QUALITY